2011
DOI: 10.1093/molehr/gar015
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of human trophoblastic spheroids is promoted by decidualized endometrial stromal cells and enhanced by heparin-binding epidermal growth factor-like growth factor and interleukin-1β

Abstract: Successful pregnancy in humans depends on deep invasion of the maternal decidua by extravillous trophoblast cells (EVTs), a process regulated by autocrine and paracrine signals in the decidual-trophoblast microenvironment. Here we examined whether trophoblast invasion is affected by decidual differentiation of endometrial stromal cells (ESC) and modulated locally by cytokines and growth factors. Trophoblast spheroids were generated from the EVT-derived cell line AC-1M88 and placed onto monolayers of either und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…For example, epithelial-mesenchymal transition is induced in the Ishikawa monolayer treated with ovarian steroids to promote JAR spheroid implantation (25). In response to growth factors and cytokines, CD82 in decidualized T-HESCs and carcinoembryonic antigen-related cell adhesion molecule-1 in AC-1M88 cells (hybridoma cells of primary EVTs and JEG-3 choriocarcinoma cells) are involved in the regulation of T-HESC and AC-1M88 cell migration and invasion (26,27). Our study further revealed a new role of decidual HtrA1 and HtrA3 in antagonizing the function of trophoblastic HtrA4, supporting a novel regulatory mechanism for decidua to modulate trophoblast invasion mediated by the GCM1-HtrA4 axis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, epithelial-mesenchymal transition is induced in the Ishikawa monolayer treated with ovarian steroids to promote JAR spheroid implantation (25). In response to growth factors and cytokines, CD82 in decidualized T-HESCs and carcinoembryonic antigen-related cell adhesion molecule-1 in AC-1M88 cells (hybridoma cells of primary EVTs and JEG-3 choriocarcinoma cells) are involved in the regulation of T-HESC and AC-1M88 cell migration and invasion (26,27). Our study further revealed a new role of decidual HtrA1 and HtrA3 in antagonizing the function of trophoblastic HtrA4, supporting a novel regulatory mechanism for decidua to modulate trophoblast invasion mediated by the GCM1-HtrA4 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our previous work has confirmed that CD82 in decidual stromal cells controls the trophoblasts invasiveness by suppressing integrinb1/mitogen-activated protein kinase (MAPK)/ ERK1/2 signal pathway in human early pregnancy (Li et al 2010). Interestingly, the decidualized ESCs support trophoblasts invasion by paracrine signals, such as HB-EGF, IL1, and LIF, which also can induce CD82 in ESCs for controlling trophoblasts invasion (Gonzalez et al 2011). Since similarity between cancer and endometriosis is valid, it appears feasible to hypothesize that the regulation of CD82 expression occurs in the eutopic endometrium that predisposes to invasion, implantation, adhesion, survival, and growth of ESC in the ectopic milieu.…”
Section: Introductionmentioning
confidence: 87%
“…Moreover, time-lapse recordings revealed that the stromal cells moved around the embryo to accommodate its expansion [33,34]. Decidualizing stromal cells have been shown to provide a more favorable matrix for trophoblast expansion than do undifferentiated cells [35], indicating that the choreography of stromal cell movement actively assists expansion. Further work showing trophoblast spheroids to expand to a greater extent when cultured on a monolayer of decidualized versus undifferentiated stromal cells provided more evidence supporting directed cell migration as a key element of the decidual phenotype [36].…”
Section: Embryo Selection: the Role Of Decidual Mi-grationmentioning
confidence: 99%